2013
DOI: 10.1021/ic401974t
|View full text |Cite
|
Sign up to set email alerts
|

Homoleptic Cerium(III) and Cerium(IV) Nitroxide Complexes: Significant Stabilization of the 4+ Oxidation State

Abstract: Electrochemical experiments performed on the complex Ce(IV)[2-((t)BuNO)py]4, where [2-((t)BuNO)py](-) = N-tert-butyl-N-2-pyridylnitroxide, indicate a 2.51 V stabilization of the 4+ oxidation state of Ce compared to [(n)Bu4N]2[Ce(NO3)6] in acetonitrile and a 2.95 V stabilization compared to the standard potential for the ion under aqueous conditions. Density functional theory calculations suggest that this preference for the higher oxidation state is a result of the tetrakis(nitroxide) ligand framework at the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
105
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(115 citation statements)
references
References 64 publications
10
105
0
Order By: Relevance
“…The η 2 -(N,O) bonding mode of the three hydroxylaminato arms was retained, and each complex contained a single molecule of THF coordinated to the central metal cation. The η 2 -(N,O) bonding mode had been observed previously by us and others in the RE(TriNOx)THF (RE = La, Ce, Nd, Dy, and Y) (28,40) (44,45). As shown in Table 1, there was a steady decrease in the metalligand bond lengths across the series, consistent with the decrease in ionic radii of the central metal cations.…”
Section: Resultssupporting
confidence: 82%
“…The η 2 -(N,O) bonding mode of the three hydroxylaminato arms was retained, and each complex contained a single molecule of THF coordinated to the central metal cation. The η 2 -(N,O) bonding mode had been observed previously by us and others in the RE(TriNOx)THF (RE = La, Ce, Nd, Dy, and Y) (28,40) (44,45). As shown in Table 1, there was a steady decrease in the metalligand bond lengths across the series, consistent with the decrease in ionic radii of the central metal cations.…”
Section: Resultssupporting
confidence: 82%
“…However, the N-O bond distance in 1 does fit in the range of similar bonding parameters reported for metal complexes coordinated by the aminoxyl anion form of the pyridyl nitroxide ligand. For example, the cerium complexes {Ce III (µ-R pyNO − )( R pyNO − ) 2 } 2 and Ce IV ( R pyNO − ) 4 reported by the Schelter group have average N-O distances of 1.37 and 1.38 Å), respectively [12,13]. The [Cu 2+ (pyNO − )(pyNO • )] + cation reported by the Ishida group has an N-O distance for the pyNO − ligand in the range of 1.4092(8)-1.423(2) Å [18].…”
Section: Solid-state Theoreticalmentioning
confidence: 99%
“…The Schelter group has reported the synthetic chemistry for a series of pyridyl-hydroxylamines ( R pyNOH) and demonstrated their redox activities [10]. Metal complexes of these ligands have been prepared for several f-block [11][12][13][14][15] and transition [16][17][18] metals. Inspired by these compounds we prepared and fully characterized aluminum complexes of the type ( R pyNO − ) 2 AlCl ( R pyNO − = N-tert-butyl-N-(2-(5-R-pyridyl))nitroxyl, R = H, CH 3 , CF 3 ) [7] and {(µ-R pyNO − )Al(CH 3 ) 2 } 2 (R = H, CH 3 ) [8] and explored their electrochemical behavior.…”
Section: Introductionmentioning
confidence: 99%
“…[68][69] Many "non-classical" tetravalent cerium molecules have also been prepared, including organometallic compounds, [70][71][72] amide, 65,70,[73][74][75][76][77][78] porphyrins [79][80][81][82][83] and a variety of other multidentate N-donor ligands. [84][85][86][87][88][89][90][91] Among these, the lanthanide sandwich molecule cerocene, (C8H8)2Ce, [92][93][94][95][96][97][98][99][100][101][102][103] has played a central role in development of electronic structure models for tetravalent cerium molecules. Theoretical, magnetic, and L3-edge XANES studies of (C8H8)2Ce resulted in observation of the Kondo effect in a single molecule -a phenomenon that is typically reserved for metals.…”
Section: Introductionmentioning
confidence: 99%
“…96,98 More recently, an in-depth chlorine K-edge X-ray absorption spectroscopy (XAS) and DFT study showed that Cl 3p and Ln 4f covalency was significant in tetravalent CeCl6 2-but virtually nonexistent in the trivalent analog, CeCl6 3-. 57 In spite of this and other notable synthetic progress, 57,72,87,98,[104][105][106] molecular Ce compounds are seldom the subject of emerging methods for physical and theoretical characterization. Molecular solids are promising candidates for further study because they can often be prepared as pure, crystalline compounds, can be designed with high symmetry, and can be modeled as a complete system without requiring periodic boundary conditions or other approximations.…”
Section: Introductionmentioning
confidence: 99%